Odpowiedź:
a
[tex](x + 2)(x + 3) = {x}^{2} + 5x + 6[/tex]
[tex](x - 5)(x + 4) = {x}^{2} - x - 20[/tex]
b
[tex]0.4x + 0.9x + 0.3x - 0.2 = 1.6x - 0.2[/tex]
[tex]3x - 0.2x + 1.7x = 3.5x[/tex]
z2
[tex]5x - 3(4 - 2x) = 5x - 12 + 6x = 11x - 12[/tex]
[tex]x = - 2[/tex]
[tex]11( - 2) - 12 = - 22 - 12 = - 34[/tex]
z3
a
[tex] {(x + 4)}^{2} = {x}^{2} + 8x + 16[/tex]
[tex] {(2x + 5)}^{2} = {4x}^{2} + 20x + 25[/tex]
b
[tex] {(x - 3)}^{2} = {x}^{2} - 6x + 9[/tex]
[tex] {(3x - 4)}^{2} = {9x}^{2} - 24x + 16[/tex]
c
[tex](x - 2)(x + 2) = {x}^{2} - 4[/tex]
[tex](5x + 7)(5x - 7) = {25x}^{2} - 49[/tex]